Abdullah Nashih Ulwan Perspective (Review of The Book Tarbiatul Aulad Fil Islam) - Ajeng Ninda Uminar; Mardiyan Susianti; Septia Wathani (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2018)
This study aims to find out how early childhood education according to Abdullah Nashih Ulwan based on his book Tarbiatul Aulad Fil Islam. This research is a library research, namely the study of information using qualitative data. Techniques for collecting data through primary and secondary documentation. Primary data is the book Tarbiatul Aulad Fil Islam, while secondary data in the form of children’s education manual in Islam by Abdullah Nashih Ulwan. Data analysis used is the method of content analysis, which is a technique to draw conclusions by trying to find the characteristics of the message and carried out objectively and systemically. Results of the study show that there are children’s rights in Islamic education, the implementation of children’s education in Islam, the method of children’s education in Islam, and educational material in the book Tarbiatul Aulad Fil Islam.